DETERMINATION MODEL OF MAXIMUM DRIVING DURATION DURING DANGEROUS GOODS TRANSPORTATION: Array - Afonin, M.; Postranskyy, T.; Bondarchuk, O. (Municipal economy of cities. Series: «Economy science», 2021)
The increase and compaction of large cities population of in Ukraine encourage the use of more resources for the construction of various settlements, as well as for the maintenance and operation of other facilities. Accordingly, the volume of cargo transportation associated with the creation and maintenance of these facilities is increasing. All new tasks related to the safety of dangerous cargo transportation are being created. The article considers the topical issue of the influence of human factors on traffic safety. It is known that in the process of road freight there are interconnected elements that form the system "driver - car - road - environment". If the technical parameters of cars and roads are known and can be predicted, then the variable parameters of the environment and the driver are further the least studied elements of this system. When transporting dangerous goods, the cost of driver error is extremely high, as accidents that can occur involving such vehicles have serious consequences. The following studies were used in the research: methods of field research to establish the values of traffic flow intensities on highways; in-house research methods to determine the value of road capacity; electrophysiological methods to determine changes in the functional state of drivers; methods of system analysis for processing the results of research and their interpretation; methods of statistical and mathematical analysis for the formation of models for determining the maximum allowable driving time of drivers who carry dangerous goods. Experimental studies of driver’s regulatory systems activity index change, considering different ages and socionic groups were carried out. This task also included study of road condition complexity impact on the driver during second class dangerous goods transportation in the settlements or out of them.